Analisis Hukum Islam tentang Pendaftaran Haji Saat Usia Dini (Kajian Terhadap Fatwa MUI dan Teori Sosial Ekonomi) - Abdullah Sani; Muhammad Hizbullah; Ardat Ardat (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the registration of hajj at this age in the study of the MUI fatwa No. 002/MUNAS X/MUI/XI/2020 and socio-economic theory studies. This study uses a qualitative research method based on literature study with primary data sources, namely the preamble of fatwa no. 002/MUNAS X/MUI/XI/2020 concerning registration of hajj at an early age and a book on economic sociology by Damsar and Indrayani. Data analysis was carried out using content analysis and description analysis techniques. The results of the study explain that Hajj registration at an early age to get a portion of the Hajj is legal (permissible), provided that the money used to register for Hajj is obtained in a lawful way, does not interfere with other costs that must be met, does not violate the provisions of the legislation. , does not hinder the implementation of Hajj for mukallaf who already have the obligation 'ala al-faur and have registered. Then the research also explains that socially registration for Hajj at an early age has the opportunity to create new social strata, where at an early age a person will be seen as respectable by his participation as a prospective Hajj participant. Whereas in the perspective of economic studies, participation from an early age can only be carried out by people with high economics.